Internalisasi Maqâshid al-Syarî’ah dalam Ekonomi Menurut M. Umer Chapra - Muhammad Yafiz (AHKAM : Jurnal Ilmu Syariah, 2015)
Islamic economic system as part of a true Islamic teachings from the beginning must have intended to establish what the objectives pensyariatannya (maqasid al-shari'ah), namely the realization of the benefit to achieve happiness in this world and in the hereafter. The purpose of Islamic economics is welfare or well-being in the field of material possessions or wealth. However, it is not understood as something separate from a form of devotion (worship) to God, so that the welfare and management of material possessions still have to refer to the values of all the Lord's and deals with aspects of the benefit of others in the maqasid al-shariah.DOI: 10.15408/ajis.v15i1.2853